Bridging the Gap between TGF-β/Smad Signalling and Tumorigenesis Arising from Clonorchis sinensis Induced Hepatic Fibrosis - Ika Nurzijah; Dina Ratna Juwita (ISCC (Indonesian Journal of Cancer Chemoprevention))
Clonorchiasis is a parasitic infection caused by food borne trematode, Clonorchis sinensis that is mainly prevalent in Asian countries, including South Korea, China, northern Vietnam, Japan, as well as far-eastern Russia, in which over 35 million people are the casualties. Clonorchiasis is characterized by the development of hepatic fibrosis. Upon chronic liver injury following the C. sinensis infection, hepatic fibrosis develops into cholangiocarcinoma with a concomitant genetic and epigenetic mutations. Cholangiocarcinoma represents important clinical manifestation of C. sinensis infection and causes high rate of morbidity. TGF- β/Smad signalling is known to initiate hepatic fibrosis following the hepatic injury. However, little is known about the role of TGF- β/Smad signalling during C. sinensis induced hepatic injury and the underlying contribution of TGF- β/Smad signalling in the development of cholangicarcinoma. The expression dynamic of TGF-β/Smad signalling and their role in the development of hepatic fibrosis in C. sinensis infected BALB/c mice have been investigated. Concomitantly but irrespective to C. sinensis infection, the role of hepatic epithelial TGF-β during hepatic fibrosis and the development of cholangiocarcinoma arising from hepatic epithelial cells have also been dissected. Both findings will be reviewed in this paper. Thereby, the link between TGF-β/Smad signalling, hepatic fibrosis during C sinensis infection, and cholangiocarcinoma could be drawn clearly.